THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Riski Eko Ardianto; Rina Nurjanah (SEAN Institute, 2023)
This study aims to examine the effect of motivation, work discipline and work environment on employee performance at PT. Anugrah Jaya Retailindo in East Jakarta. The research sample was 60 people and data were collected using a questionnaire questionnaire method. The data analysis technique used multiple linear regression test. The results of this study; The data were obtained using a questionnaire instrument and have been tested for validity and reliability. The examiner of this data was analyzed using multiple linear regression, and hypothesis testing was carried out by t-test and f-test. The results of the study based on partial testing showed that motivation had a positive and significant effect on employee performance, the value of Sig = 0.000 and tcount of 3.888 while ttable = 1.670 because the value of Sig < 0.05 and tcount> ttable then H1 was accepted. Work Discipline has a positive and significant effect on employee performance, obtained the value of Sig = 0.008 and tcount 2.730 while ttable = 1.670 because the value of Sig < 0.05 and tcount> ttable then H2 is accepted. The work environment has no positive and significant effect on employee performance, the value of Sig = 0.876 and tcount 0.157 while ttable = 1.670 because the value of Sig > 0.05 and tcount < ttable then H3 is rejected. Simultaneous testing shows that motivation, work discipline and work environment have a positive and significant effect on employee performance at PT. Anugrah Jaya Retailindo in East Jakarta.